2007
DOI: 10.2109/jcersj.115.304
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Contact Damages of Nanostructured Silicon Carbide Ceramics

Abstract: Three types of nanostructured silicon carbide ceramics were prepared with additives of Al 2 O 3 and Y 2 O 3 as the primary sintering additives, together with 1 mass! CaO, 1 mass! MgO or 0.73 mass! AlN. The silicon carbides SiC containing tens of nanometers of grains were successfully fabricated using a two-step sintering process. The mechanical properties and contact damages of the nanostructured SiC ceramics were investigated in this study. The nanostructured SiC ceramics exhibited a hardness of Ĭ20 GPa, a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…As pointed out by several authors, [2][3][4][5][6][7][8][9] another promising way to enhance the mechanical performance might be the reduction of grain size down to the nanosize range. In the light of this, a large amount of works focusing on the synthesis and consolidation of bulk nanostructured silicon carbide was recently performed with regard to the Hall-Petch relation predicting a substantial increase in yield strength and hardness for nanoscaled microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out by several authors, [2][3][4][5][6][7][8][9] another promising way to enhance the mechanical performance might be the reduction of grain size down to the nanosize range. In the light of this, a large amount of works focusing on the synthesis and consolidation of bulk nanostructured silicon carbide was recently performed with regard to the Hall-Petch relation predicting a substantial increase in yield strength and hardness for nanoscaled microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…The fracture stress of the SiC hemispherical shell specimen was calculated from the critical load for the cracking of the shell. Finite element (FE) analysis was used to derive a semiempirical equation for the stress calculation and the detailed procedure is given elsewhere [13]. In brief, the FE analysis was performed using a commercial program, ABAQUS.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…The crack propagation path was therefore extended, and the toughness of the coating was improved. It is well established that toughening mechanisms such as crack deflection and crack trapping can improve the crack growth resistance of bulk brittle materials markedly [26,29,30]. Therefore, it could be concluded that the improvement of the crack growth resistance was attributed to the three-dimensional network structure present in the nanocomposite coating.…”
Section: Properties Of the Coatings And Toughening And Strengtheningmentioning
confidence: 99%
“…During plastic deformation, grain boundaries (GBs) in nanocrystalline materials serve as sources of partial lattice dislocations and cracks often nucleate at and grow along interfaces. The intergranular network thin film with amorphous structure, however, could improve the strength and toughness of the three-dimensional network structure by intercrystalline strengthening and toughening [29][30][31][32]. Therefore, the three-dimensional network structure may work as reinforcing and toughening units in the ceramic coating, improving the strength and toughness of the coating.…”
Section: Properties Of the Coatings And Toughening And Strengtheningmentioning
confidence: 99%